Alcohol consumption and sports-betting among young male motorcycle taxi boda boda riders in urban southwestern Uganda - Nabifo, Stella Cheryl; Izudi, Jonathan; Bajunirwe, Francis (BMC Public Health, 2021)
Background: The popularity of sports-betting is growing globally and may be associated with alcohol consumption among young adults. In this study, we examine the relationship between alcohol consumption plus other substances with sports-betting in a group of young adult males in Uganda. Methods: We conducted a cross-sectional study and interviewed male motorcycle taxi boda boda riders in the southwestern Uganda town of Mbarara. We asked questions about alcohol consumption, smoking plus history and frequency of sports-betting. Results: We enrolled 401 riders. The median age was 29.0 years, interquartile range 25–32 years. Seventy-four (18.5%) had engaged in sports-betting in the past 30 days. Among those that reported sports-betting, 16(21.6%) engaged daily or almost daily. Alcohol use was significantly associated with sports-betting with an adjusted risk ratio (aRR) of 2.08(95% CI 1.36, 3.18) among moderate drinkers but not among heavy drinkers in comparison to low or non-drinkers. Cigarette smoking was significantly associated with sports-betting with an aRR 1.85(95% CI 1.13, 3.01). Conclusion: Sports-betting is common among these young male motorcycle riders, and is associated with both alcohol consumption and cigarette smoking. Interventions to regulate sports-betting may be co-packaged with those to reduce alcohol consumption and cigarette smoking among young adult males
Keywords: Sports-betting; Alcohol consumption; Uganda; Young males